Is the KLSE efficient? Efficient market hypothesis vs behavioral finance - Md. Nassir, Annuar (2002)
Over the last 100years since Bachelier (1900)pioneering work on Random Walk Hypothesis, studies on the Efficient Market Hypothesis (EMH) have revealed mixed evidence. EMH states that stock prices reflect information. In an efficient market the prices of stocks reflect a rational assessment of the underlying worth of stocks. On average you will make money but the money you make is just enough to cover the risk you have assumed. If markets are efficient then new information is reflected quickly into market prices. Conversely, if markets are inefficient, information is reflected only slowly into market prices, if at all. EMH also presupposes an ability to detect incorrectly priced securities and profitable arbitraging opportunities which move the market towards efficiency. After the first marginal investor had profited from a price increase (or decrease), subsequent investors with the same information obtain no significant profits. This means that, in general, majority of investors cannot consistently profit from any delays in price adjustment reflecting new information. However continuous stream of well-documented evidence from the behavioural finance literature suggest that markets are inefficient. This paper attempts to review this controversy based on world evidence at large and with special reference to the Kuala Lumpur Stock Exchange and offers suitable panacea to rationalize this phenomena.